Derating design for optimizing reliability and cost with an application to liquid rocket engines. (February 2016) - Kim, Kyungmee O.; Roh, Taeseong; Lee, Jae-Woo; Zuo, Ming J.
Abstract: Derating is the operation of an item at a stress that is lower than its rated design value. Previous research has indicated that reliability can be increased from operational derating. In order to derate an item in field operation, however, an engineer must rate the design of the item at a stress level higher than the operational stress level, which increases the item׳s nominal failure rate and development costs. At present, there is no model available to quantify the cost and reliability that considers the design uprating as well as the operational derating. In this paper, we establish the reliability expression in terms of the derating level assuming that the nominal failure rate is constant with time for a fixed rated design value. The total development cost is expressed in terms of the rated design value and the number of tests necessary to demonstrate the reliability requirement. The properties of the optimal derating level are explained for maximizing the reliability or for minimizing the cost. As an example, the proposed model is applied to the design of liquid rocket engines. Abstract : Highlights: Modeled the effect of derating design on the reliability and the development cost. Discovered that derating design may reduce the cost of reliability demonstration test. Optimized the derating design parameter for reliability maximization or cost minimization.